2020
DOI: 10.1039/c9sc05492h
|View full text |Cite
|
Sign up to set email alerts
|

A simple and efficient approach toward deep-red to near-infrared-emitting iridium(iii) complexes for organic light-emitting diodes with external quantum efficiencies of over 10%

Abstract: The simplest and the most efficient deep-red to near-infrared-emitting emitters afford a new record external quantum efficiency for iridium(iii) complex based deep-red to near-infrared organic light-emitting diodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 40 publications
(93 reference statements)
0
93
0
Order By: Relevance
“…Therefore, some electron‐withdrawing CN groups are introduced into the organic framework of TFB to achieve two unreported polymers (Figure 1a). [ 34,35 ] The 2‐cyanopropan‐2‐yl (CNPr) group was chosen for its unique features, such as weak electron‐withdrawing property and no active hydrogen (α– H ) atoms. The former decreases the electrons on the polymer chain, resulting in a much more stabilized HOMO energy level.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, some electron‐withdrawing CN groups are introduced into the organic framework of TFB to achieve two unreported polymers (Figure 1a). [ 34,35 ] The 2‐cyanopropan‐2‐yl (CNPr) group was chosen for its unique features, such as weak electron‐withdrawing property and no active hydrogen (α– H ) atoms. The former decreases the electrons on the polymer chain, resulting in a much more stabilized HOMO energy level.…”
Section: Resultsmentioning
confidence: 99%
“…Many works have been done to the design and preparation of noble metal-based PTMCs toward highly efficient OLEDs. [77][78][79][80][81][82] So far, many commercialized emitters are based on these phosphors (such as iridium(III) complex). [83][84][85][86][87][88] However, these noble metals often have some disadvantages (such as high cost and low abundance in nature).…”
Section: Organic Light-emitting Diodesmentioning
confidence: 99%
“…We and other group have demonstrated that the cyano group (À CN) is of electron withdrawing property which can lower the energy level of the lowest unoccupied molecular orbital (LUMO) and tune the molecular emission spectra. [44,47] Accordingly, the À CN group was anchored to the Nz to push the emission to the longer wavelength region and the resultant molecule is abbreviated as PINzPCN. It showed similar PLQY with PINzP in both doped and nondoped films but more redshifted emission.…”
Section: Introductionmentioning
confidence: 99%
“…The doped device of PINzP exhibited similar EL spectra to nondoped device but much improved efficiency with a maximum EQE of 6.96%. We and other group have demonstrated that the cyano group (−CN) is of electron withdrawing property which can lower the energy level of the lowest unoccupied molecular orbital (LUMO) and tune the molecular emission spectra [44,47] . Accordingly, the −CN group was anchored to the Nz to push the emission to the longer wavelength region and the resultant molecule is abbreviated as PINzPCN.…”
Section: Introductionmentioning
confidence: 99%